2010
DOI: 10.1590/s0004-282x2010000600008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of headache in undergraduate students in Southern Brazil

Abstract: Objective: To determine the prevalence, characteristics and impact of headache among university students. Method: The criteria established by the International Headache Society were used to define the primary headache subtypes and the Migraine Disability Assessment Questionnaire (MIDAS), to assess the disability. The students were then grouped into six categories: [1] .5% had at least one headache episode in the last three months. Regarding disability, there was a significant difference between the headache t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 18 publications
7
42
3
1
Order By: Relevance
“…Students of several courses were selected, of whom, 813 presented headache, being for migraine a prevalence of 6,9%, and inferior when compared to other studies. (7) Regarding the duration of the migraine crisis, which is characterized for migraine without aura from 4 to 72 hours, it occurred in 90% of "4 to 24 hours" and 10% of "1 to 3 days" in academics of this study (Table 1), corroborating with the results of Andrade et al who demonstrated that this characteristic occurred in 100% of medical students in the city of Barbacena. (14) Different of Adoukonou et al who in the city of Parakou (West Africa) demonstrated that university students presented 62% of this characteristic for migraine without and with aura, and the two migraines were not separated as to the duration of the crisis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Students of several courses were selected, of whom, 813 presented headache, being for migraine a prevalence of 6,9%, and inferior when compared to other studies. (7) Regarding the duration of the migraine crisis, which is characterized for migraine without aura from 4 to 72 hours, it occurred in 90% of "4 to 24 hours" and 10% of "1 to 3 days" in academics of this study (Table 1), corroborating with the results of Andrade et al who demonstrated that this characteristic occurred in 100% of medical students in the city of Barbacena. (14) Different of Adoukonou et al who in the city of Parakou (West Africa) demonstrated that university students presented 62% of this characteristic for migraine without and with aura, and the two migraines were not separated as to the duration of the crisis.…”
Section: Discussionsupporting
confidence: 91%
“…Bigal et al (6) , found a prevalence of 25% of migraine in Brazil and they also observed that the students with migraine showed a decrease of 62,7% in productivity in comparison with a decrease of 24,4% in the ones with episodic tensiontype headache. (7) Migraine has a significant impact on the quality of life, the health resources, and the professional and personal activities of patients. (8) Some studies on the prevalence of migraine have reported that migraine may be more common in college students than in other social groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies focus on one category of illness. For example, the prevalence and characteristics of headache in Brazil [16], Europe [17], Nigeria [18], and Turkey [19], the trigger factors for headache [20], and the relationship between stress and gastrointestinal upset and headaches [21,22], and anorexia [23].…”
Section: Introductionmentioning
confidence: 99%
“…Headaches are very important due to disruptions in daily tasks, decreasing working efficiency, and the use of pain-relief medication (6). The high prevalence of this disorder has a very significant effect on job performance as well as quality of life and imposes a great economic burden on society (4, 7). …”
Section: Backgroundsmentioning
confidence: 99%